Motivasi Masyarakat Melakukan Aktivitas Fisik Di Masa Pandemi Covid-19 - Mega Wulandari; Yetty Septiani Mustar; Pudjijuniarto Pudjijuniarto; Indra Himawan Susanto; Agus Hariyanto (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
COVID-19 affects various aspects of life including the continuity of physical activity in various countries. One of the impacts most felt by the community is the existence of social restrictions that make people tend to experience a decrease in physical activity during the COVID-19 pandemic. This study aims to identify the motivation of the community in carrying out physical activities in the community in Gresik district. This type of research is descriptive quantitative using survey method. The research sample was 212 people with an age range of 17-55 years. The data collection technique used a motivation for physical activity and motivation for exercise/workout questionnaire. The results of this study indicate that the motivation of the community to do physical activity during the COVID-19 pandemic in the majority of men is in the sufficient category, which is 86 (74.1%) and the majority of women are in a good category, which is 30 (14.2%). Furthermore, the indicator of the intrinsic motivation factor of the community doing physical activity is mostly influenced by pleasure, namely 91.3% for men and 93.75% for women, while the majority of extrinsic motivation factors are influenced by the environment, namely 79.3% for men and 72.9 for women.